Odyssey of Childhood from the Pages of August Kranti A Narrative of Students’ Participation - Srivastava, Gouri (INDIAN EDUCATIONAL REVIEW, 2025)
The freedom struggle of India had many phases and personalities, both known and lesser known, who contributed in making the movement memorable for all time. In the Quit India Movement, popularly known as the August Kranti, the students and children played a significant role. The government records, private paper, oral accounts and newspaper clippings mention their engagement with different phases of the movements. However, the spaces allocated to them are often minuscule. The names of some of the children who laid down their lives are sometimes referred to, but very often the finer details of their roles are often glossed over. Nevertheless, the manner of their participation did capture the attention of authorities, and thus, the names of the few who became the legend makers for all time are mentioned. In this paper, an attempt has been made to weave the role of the students in varying age groups and to discuss the nature of their involvement in different provinces.